METHOD OF COLLECTING TEXTS FROM RELIGIOUS PAGES ON TWITTER SOCIAL NETWORK - Mussiraliyeva , Ш.Ж.; Ospanov , Р.Қ.; Shalabaev , Қ.М.; Sattar , Б.Ә. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
Currently, social networks are a platform for a large amount of information. With the exception of useful information, social networks have become a convenient platform for illegal actions. Suspicious activity often remains in the shadows due to the lack of threat detection and analysis systems in social networks. The article provides a brief overview of approaches for analyzing information from a user profile.